Peningkatan Hasil Belajar Matematika Materi Pengukuran Sudut Bangun Datar Dengan Media Quizizz Mode Kertas Kelas 4 SD Negeri 33 Mataram - Silvia Rizkika Eprina; Hari Witono; Sri Lestari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Samawa, 2023)
This research was motivated by the low results of learning mathematics in the material measuring angles of flat shapes. The average score of student evaluation results on mathematics subject matter is still low, student learning completion only reached 59% or 11 students completed out of a total of 28 students. This research aims to improve learning outcomes in mathematics subjects measuring angles of flat shapes in class IV A of SD Negeri 33 Mataram, this of course requires improvements in the learning process through quantitative research with Pre-Experimental Design in the form of One-Group Pretest Posttest Design research. The population of this study were all students in class IV A of SD Negeri 33 Mataram. The sample for this research consisted of 28 IV A students. In the experimental class, they were given treatment in the form of applying the interactive game learning media Quizzizz in their learning. The instrument used to measure students' mathematics learning outcomes is a multiple-choice test. The results of research data analysis answer the research hypothesis. With the average class score increasing from before the treatment was given. It can be concluded that there is an increase in Mathematics Learning Outcomes on Measuring Angles of Flat Figures Using Quizizz Paper Mode Media for Class 4 of SD Negeri 33 Mataram.